Practice of Dengue Prevention among School-Aged Children in Indonesia - Hendra, Agus; Heriani, Winda; Perdani, Agni Laili (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2020)
Purpose: This study aims to determine the practice of dengue prevention among school-aged children in IndonesiaMethodology: This study is quantitative research with a cross-sectional approach and conducted in May 2020. The total of 230 subjects school-aged children recruited in the study by using a convenience sampling. Data collection using the Self Efficacy Questionnaires (Practice For Dengue Fever) with Cronbach’s alpha > 70.Results: Most of the respondents cleaned the area around the house (92.2%), wear long sleeves and long pants to prevent mosquito bites (82.2%). A small percentage (31%) use mosquito nets while sleeping, put abates or chemicals to kill mosquitoes in water storage (32.4%), and spray dark places with insect vendors and half of them (59.4%). use mosquito nets while sleepingApplication: The need for support and assistance from healthcare professionals in primary school to practice dengue prevention.